PENGARUH PERBANDINGAN ANTIKOAGULAN EDTA DAN VOLUME DARAH YANG TIDAK SESUAI PADA PEMERIKSAAN HEMOGLOBIN, ERITROSIT, DAN TROMBOSIT PADA PASIEN MEDICAL CHECK UP DI RS PERTAMINA CILACAP - Kartika Palupi; Meka Faizal Farabi; Dini Puspodewi (Klinikal Sains : Jurnal Analis Kesehatan, 2025)
Medical Check Up (MCU) is a procedure intended to determine the overall health condition. The results of this examination can be a reference for companies to measure the physical ability of employees to perform tasks. The purpose of this study was to determine the effect of the use of EDTA anticoagulant that was not in accordance with blood volume on the examination of hemoglobin, erythrocytes, and platelets in Medical Check Up patients at RSPC. The research sample was taken using purposive sampling technique consisting of 33 Medical Check Up patients.This study is an observational analytic study with cross sectional method. The results showed that the average hemoglobin level of 2 ml blood volume in EDTA vacutainer tubes was 15.488 g/dL while the average hemoglobin level of 3 mL blood volume in EDTA vacutainer tubes was 15.515 g/dL and the Paired Sample T-Test test showed no significant difference (p>0.05). The average erythrocyte level of 2 ml blood volume in EDTA vacutainer tubes is 5.518 million /µL, while the average erythrocyte level of 3 mL blood volume in EDTA vacutainer tubes is 5.117 million /µL and the Paired Sample T-Test test shows no significant difference (p>0.05). The average platelet level of 2 ml blood volume in EDTA vacutainer tubes is 274.576 thousand/µL while the average platelet level of 3 mL blood volume in EDTA vacutainer tubes is 267.970 thousand/µL and from the Wilcoxon Signed Rank Test which shows that there is a significant difference in platelet levels (p<0.05).